2002
DOI: 10.1094/phyto.2002.92.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Origin of Resistance toXanthomonas campestrispv.campestrisinBrassicaGenomes

Abstract: Two hundred and seventy-six accessions of mainly Brassica spp. were screened for resistance to Xanthomonas campestris pv. campestris races. In Brassica oleracea (C genome), the majority of accessions were susceptible to all races, but 43% showed resistance to one or more of the rare races (2, 3, 5, and 6) and a single accession showed partial resistance to races 1, 3, 5, and 6. Further searches for resistance to races 1 and 4, currently the most important races worldwide, and race 6, the race with the widest h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
105
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 17 publications
6
105
0
Order By: Relevance
“…Nine races of Xcc have been identified to date from pathogenicity tests based on the interaction between differential cultivars and races [5][6][7][8][9]. [7] reported that the appearance of race 1 and 4 was predominant worldwide and other races, 2, 3, 5 and 6, were rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine races of Xcc have been identified to date from pathogenicity tests based on the interaction between differential cultivars and races [5][6][7][8][9]. [7] reported that the appearance of race 1 and 4 was predominant worldwide and other races, 2, 3, 5 and 6, were rare.…”
Section: Introductionmentioning
confidence: 99%
“…Screening for Xcc resistance was performed in Brassica species and related species [11][12][13][14] and extensive screening using more than 100 genotypes was done by [8]. As a result, resistance to Xcc has been identified in genotypes of B. rapa (A genome), B. nigra (B), B. oleracea (C), B. carinata (BC), B. juncea (AB), and B. napus (AC).…”
Section: Introductionmentioning
confidence: 99%
“…The predominance of races 1 and 4 can be attributed to wide cultivation of B. oleracea cultivars that are susceptible to these races. This is also supported by the lack of observation of symptoms on B. carinata which has been reported to display resistance to races 1 and 4 (Taylor et al, 2002). The limited observation of race 1 in Tanzania and absence in Uganda could be attributed to the small sampling population.…”
Section: Discussionmentioning
confidence: 79%
“…Management of this disease is mainly based on using pathogen-free planting material (seeds or transplants) and eliminating potential sources of inoculum especially crop debris and cruciferous weeds (Taylor et al, 2002). However, Xcc is a seed-borne pathogen that is difficult to eliminate from seeds (Roberts et al, 1999) and therefore pathogen-free planting material is not always available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation